Exploring physics of ferroelectric domain walls via Bayesian analysis of atomically resolved STEM data - Christopher T. Nelson (Nature Portfolio, 2020)
Ferroelectric domain wall profiles can be modeled by phenomenological Ginzburg-Landau theory, with different candidate models and parameters. Here, the authors solve the problem of model selection by developing a Bayesian inference framework allowing for uncertainty quantification and apply it to atomically resolved images of walls. This analysis can also predict the level of microscope performance needed to detect specific physical phenomena.